PENERAPAN MANAJEMEN KINERJA DALAM SUMBER DAYA MANUSIA PADA UMKM CAFE UNCLE JACK - Tara Chairunnisya; Tri Ayu Cahyani Putri; Hery Setiawan; Jefri Akbar (Universitas Kristen Indonesia Toraja, 2022)
Performance Management is a procedure related to how to guide and develop the quality of employees at work. Where, the work of employees becomes a benchmark for the company’s budgeting system. By optimizing performance, good performance management is needed to realize the company’s goals. The research subject is Cafe Uncle Jack, has been operating for 5 years (2017) as a culinary business and consists of Mrs. Lina as Leader, Mrs. Lini as Manager, Barista, Cashier, Waitress, and Cooker. The purpose of this study is to evaluate the management of human resources at Cafe Uncle Jack including several series of activities provided by the new employment. In a series of activities that occur in Uncle Jack’s Cafe, a qualitative descriptive method will be formulated in the form of interviews related to performance management. Based on the results of the interview, Cafe Uncle Jack gives full attention ti it’s employees so that the quality of performance and customer satisfaction can be guaranteed.